1999
DOI: 10.1109/82.752953
|View full text |Cite
|
Sign up to set email alerts
|

Robust adaptive filtering algorithms for α-stable random processes

Abstract: A new class of algorithms based on the fractional lower order statistics is proposed for finite-impulse response adaptive filtering in the presence of-stable processes. It is shown that the normalized least mean p-norm (NLMP) and Douglas' family of normalized least mean square algorithms are special cases of the proposed class of algorithms. A convergence proof for the new algorithm is given by showing that it performs a descent-type update of the NLMP cost function. Simulation studies indicate that the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…On the basis of the GNLMP algorithm 10 and our previous work (the FxMNLMP algorithm 9 ), we have proposed a FxMGNLMP algorithm for impulsive ANC. The simulation results (presented in Sec.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the GNLMP algorithm 10 and our previous work (the FxMNLMP algorithm 9 ), we have proposed a FxMGNLMP algorithm for impulsive ANC. The simulation results (presented in Sec.…”
Section: Discussionmentioning
confidence: 99%
“…Hereafter, the resulting algorithm is referred to as the filtered-x modified normalized least mean p-power (FxMNLMP) algorithm. 9 As a generalization to the NLMP update equation, the following update equation for the generalized normalized least mean p-power (GNLMP) is proposed: 10 wðn þ 1Þ ¼ wðnÞ þ lðnÞpðeðnÞÞ hai ðxðnÞÞ hðqÀ1Þai ;…”
Section: Flom-based Algorithms For Anc Of Impulsive Noisementioning
confidence: 99%
“…Furthermore, the normalized LMP (NLMP) and generalization of the NLMP algorithms based on the fractional lower-order statistics (FLOS) are proposed in [21][22][23]. The LMP family algorithms have been successfully employed for system identification under impulsive noise disturbances [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hence impulsive noise produces more outliers than expected under the Gaussian assumption, degrading the performance of linear filtering. Several studies [1][2][3][4][5] showed that α-stable distribution is better for modeling impulsive noise than Gaussian distribution in signal processing for it has some important characteristics. Many types of noises are well modeled as α-stable distributed processes, including underwater acoustic, low-frequency atmospheric, and many man-made noises.…”
Section: Introductionmentioning
confidence: 99%